1996
DOI: 10.2337/diab.45.4.488
|View full text |Cite
|
Sign up to set email alerts
|

Phenotypic Modulation of the Mesangium Reflected by Contractile Proteins in Diabetes

Abstract: The phenotypic change of the mesangial cell is considered to play a pivotal role in the accumulation of extracellular matrix in diabetic nephropathy. This investigation was undertaken to evaluate the expression of the various isoforms of contractile proteins in the streptozocin (STZ)-induced diabetic rat kidney and in renal biopsy specimens from patients with diabetic nephropathy. Specific antibodies to myosin heavy chain isoforms (SM1, SM2, SMemb), caldesmon, and alpha-smooth muscle actin and cDNAs for SMemb … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
27
1
2

Year Published

1998
1998
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 78 publications
(30 citation statements)
references
References 35 publications
0
27
1
2
Order By: Relevance
“…Recently, Doi et al [29]demonstrated that overexpression of CNP in cultured SMCs by adenovirus-mediated gene transfer caused growth inhibition of SMCs at the G1 phase with phenotype modulation. GMC phenotype change has been suggested to be associated with glomerular hypercellularity and sclerosis [30, 31]. CNP may exert its suppressive effects such as antiproliferative action and inhibition of type IV collagen secretion by changing GMC phenotype.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Doi et al [29]demonstrated that overexpression of CNP in cultured SMCs by adenovirus-mediated gene transfer caused growth inhibition of SMCs at the G1 phase with phenotype modulation. GMC phenotype change has been suggested to be associated with glomerular hypercellularity and sclerosis [30, 31]. CNP may exert its suppressive effects such as antiproliferative action and inhibition of type IV collagen secretion by changing GMC phenotype.…”
Section: Discussionmentioning
confidence: 99%
“…Thirty glomeruli in each section were graded from 0 to 4+ by two blinded observers as follows: 0, none; 1, trace mesangial staining; 2, weak mesangial staining; 3, moderate mesangial staining; 4, strong mesangial staining, as previously reported [7]and data were mean ± SD.…”
Section: Methodsmentioning
confidence: 99%
“…They play physiologically important roles by supporting glomerular structure and controlling capillary tone [1, 2, 3]. In various glomerular diseases, phenotypic changes of MC have been observed in association with mesangial proliferation and interstitial collagen accumulation [4, 5, 6, 7, 8, 9, 10, 11]. This particular phenotype has been called ‘myofibroblast-like’, which is closely related to the progression of glomerular sclerosis [9, 10, 11].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The distribution of various ECM components and TGF-β was studied by using indirect immunofluorescence techniques as previously described [20]. …”
Section: Methodsmentioning
confidence: 99%